- #1

- 2

- 0

Assuming

Y = a + b*X + errorTerm

Z = c + d*X + errorTerm,

Y = g + h*Z + errorTerm;

what can we say about the relationtion between h and (b,d)? under what

condition so we can have "h = b/d"?

thanks

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter liujx80
- Start date

- #1

- 2

- 0

Assuming

Y = a + b*X + errorTerm

Z = c + d*X + errorTerm,

Y = g + h*Z + errorTerm;

what can we say about the relationtion between h and (b,d)? under what

condition so we can have "h = b/d"?

thanks

- #2

- 36,173

- 6,792

Y = a + b*X + errorTerm

Z = c + d*X + errorTerm

Y = g + h*(c + d*X + errorTerm

whence:

g = a - h*c

h = b/d

errorTerm

But perhaps you mean b, d and h to be the estimated parameters. That gets more subtle.

- #3

chiro

Science Advisor

- 4,790

- 132

Following on from haruspex's post above, are you trying to estimate them or do you know them already? If you are estimating them, do you have a specific distribution or analysis in mind? Do you have priors?

- #4

- 2

- 0

Thanks

Share: